Direct Learning Model to Improve Students’ Mathematics Learning Outcomes: A Classoom Action Research - Fatkatul Muawanah; Bambang Arianto; Dwilita Astuti; Khabib Kholikovich Razzokov (CV. Creative Tugu Pena, 2022)
This article was to improve the student learning outcomes in the teaching and learning process thrugh direct learning model. The sample research was 32 students. The research used Classroom Action Research that conducted in two cycles. It consisted of four steps namely, planning, acting, observing, and reflecting. The procedures of research were performs by administrating two cycles. Each cycle contain four steps which are planning, action, observation, and reflection. The collecting data used test, observation, and interview. Analyzing data was calculated using simple statistics. The result showed that through direct learning models can streamline the teaching and learning process in the classroom in terms of student learning outcomes which continue to increase from the results of the pre-cycle 6.25%, the first cycle of 68.75%, and the second cycle of 90.63%. Based on the research findings, it can be concluded that the direct learning model can improve student learning outcomes, especially in mathematics subjects on the subject of fractions at MI Tarbiyatul Athfal Pasir Sakti. Keywords: Direct Learning Model, Learning Outcome, Classroom Action Research